2015
DOI: 10.5846/stxb201306031280
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of changes of ecosystem services of Tai Lake in recent 10 years

Abstract: Lake ecosystem in Tai Lake (CH: Taihu) provide people with both direct and indirect benefits which are called ecosystem services. However, lake ecosystem services in Tai Lake have not well recognized and accurately quantified in past years. Decades of wastewater discharge, industrial pollution, and over application of chemical fertilizers around the basin have transformed this once meso鄄oligotrophic lake in the 1950s into its present hypertrophic state. As a result, cyanobacteria blooms appear during every sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…A previous study has observed an increasing tendency of total value of ecosystem service of Tai Lake [85]. This study finds that the counties adjacent to Tai Lake, such as Wuxi, Suzhou, and Yixing, showed an ESV increase or minimal ESV loss, but we did not observe significant spatial spillover effect of these counties.…”
Section: Spatial Spillover Effectscontrasting
confidence: 67%
“…A previous study has observed an increasing tendency of total value of ecosystem service of Tai Lake [85]. This study finds that the counties adjacent to Tai Lake, such as Wuxi, Suzhou, and Yixing, showed an ESV increase or minimal ESV loss, but we did not observe significant spatial spillover effect of these counties.…”
Section: Spatial Spillover Effectscontrasting
confidence: 67%